Enhancing the Awareness of Indonesian Students in Hualien City, Taiwan, on Maintaining Health During their Studies from an Islamic Perspective - Taufani, Indra Putra; Hadning, Ingenida; Haris, Fahni; Yang, Liang-Yo (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
The effectiveness of students' diets, levels of exercise, and other healthy behaviors are strongly correlated with their learning processes, which in turn influence their academic performance. The real issue is the students' hectic schedules and precarious financial situations, which frequently harm their sleep and nutrition quality. This paper discussed the significance of teaching students the value of maintaining their dietary intake, physical activity levels, and sleep schedules. Students frequently put their academic activities and part-time jobs as priorities without considering the associated health risks. Therefore, we propose an activity integrating scientific and Islamic perspectives to educate students about health-related matters. The activity includes presentations on sleep patterns, nutrition, and hydration, integrating scientific research with teachings from the Quran and Hadith. Students are encouraged to engage in discussions and share experiences related to the material. When the community service program with Indonesian students in Taiwan was evaluated, it became clear that participants' knowledge and comprehension had significantly improved. According to the article's conclusion, the program successfully raised participant awareness of the value of staying healthy while studying from an Islamic perspective.